(untitled) (Czech Journal of International Relations, 1966)
On days 20—22. May 1966 was held in Brussels II. European conference of the Society for International Development (SID). This society is an international organization, bringing together 5,000 individual (scientific, economic and political workers) and collective members (various institutions, national and international organizations); it was founded in the United States on the basis of the Ford Foundation. With its program, the Society aims to act as a forum for the exchange of thoughts and experiences between persons who professionally deal with basic problems of economic and social development in modern society. Recently, society’s attention has been turning especially to the issue of developing countries.